Plan de desarrollo y ordenamiento territorial (PDOT) para la parroquia Gualel, perteneciente al cantón Loja. - Angamarca Angamarca, Blanca Mercedes (2011)
The Plan of Development and Territorial Classification of Gualel are a document where he/she is reflected the reality in that the Parish is developed. It arises with the necessity of carrying out the diagnosis of the current situation in which the territory is, to discover the problems, potentialities and to outline the solutions in the mark of the knowledge of the problem of the Parish. For the elaboration of this Plan it is necessary to have the support of the social different actors and institutions that offer the pertinent information for their correct elaboration. Finally the outlined projects are not more than the necessities settled down by the same population to fulfill the objectives of the National Plan of Good to Live and this way to improve the quality of life of the Population of Gualel.